1986
DOI: 10.1128/iai.53.3.480-485.1986
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-independent activation of the classical pathway of human serum complement by lipid A is restricted to re-chemotype lipopolysaccharide and purified lipid A

Abstract: Incubation of most bacterial lipopolysaccharides (LPS) with normal human sera at 37C activates the serum complement system, resulting in decreased levels of hemolytic complement. A panel of R-chemotype LPS preparations isolated from Salmonella minnesota rough mutant strains, as well as smooth wild-type LPS from S. minnesota, Escherichia coli 055-B5, Serratia marcescens, and Yersinia enterolitica, were used to examine the effect of LPS polysaccharide chain length on LPS lipid (lipid A)-dependent activation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…The amount of fluid-phase L. pneumophila LPS required to activate complement in NHS is in agreement with the findings of several groups working with LPSs from other bacteria (6,13,32). Although we used LPS at concentrations of 1 mg/ml in most of the experiments described in this report, as little as 10 ,ug of LPS per ml was sufficient to activate the classical complement pathway.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…The amount of fluid-phase L. pneumophila LPS required to activate complement in NHS is in agreement with the findings of several groups working with LPSs from other bacteria (6,13,32). Although we used LPS at concentrations of 1 mg/ml in most of the experiments described in this report, as little as 10 ,ug of LPS per ml was sufficient to activate the classical complement pathway.…”
Section: Resultssupporting
confidence: 89%
“…These data suggested that the anti-LPS antibodies described here may be natural antibodies. We (24) and others (32) have noted that natural antibodies have low affinities and are difficult to remove by adsorption. Vukajlovich (32) reported that all NHS contains natural anti-rabbit E antibodies of the IgG and IgM classes that cross-react with antigenic determinants found on LPS polysaccharide.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations